Global DNA methylation profiling of manganese-exposed human neuroblastoma SH-SY5Y cells reveals epigenetic alterations in Parkinson’s disease-associated genes - Tarale, Prashant; Sivanesan, Saravanadevi; Daiwile, Atul P.; Stöger, Reinhard; Bafana, Amit; Naoghare, Pravin K.; Parmar, Devendra; Chakrabarti, Tapan; Kannan, Krishnamurthi (Springer, 2016)
Manganese (Mn) is an essential trace element required for optimal functioning of cellular biochemical pathways in the central nervous system. Elevated exposure to Mn through environmental and occupational exposure can cause neurotoxic effects resulting in manganism, a condition with clinical symptoms identical to idiopathic Parkinson’s disease. Epigenetics is now recognized as a biological mechanism involved in the etiology of various diseases. Here, we investigated the role of DNA methylation alterations induced by chronic Mn (100 µM) exposure in human neuroblastoma (SH-SY5Y) cells in relevance to Parkinson’s disease. A combined analysis of DNA methylation and gene expression data for Parkinson’s disease-associated genes was carried out. Whole-genome bisulfite conversion and sequencing indicate epigenetic perturbation of key genes involved in biological processes associated with neuronal cell health. Integration of DNA methylation data with gene expression reveals epigenetic alterations to PINK1, PARK2 and TH genes that play critical roles in the onset of Parkinsonism. The present study suggests that Mn-induced alteration of DNA methylation of PINK1–PARK2 may influence mitochondrial function and promote Parkinsonism. Our findings provide a basis to further explore and validate the epigenetic basis of Mn-induced neurotoxicity.